Intercultural Communication in the Professional Training of Master's Students: Concept and Structure of a Joint Educational Project - Csaba Földes; Valentina P. Furmanova (National Research Mordova State University, 2020)
Introduction. The area of intercultural communication with its system-forming theory, empirical research and implementation is gaining currency both in academic research and in the professional training of students. Regarding the latter aspect, there is a need (a) for developing a concept for the training of master's students with knowledge of foreign languages; (b) for the introduction of new educational practices that successfully combine intercultural communication, foreign language and the modeling of communicative behavior in foreign language communication with its further reproduction in language practice in the students' native language as well as (c) for the introduction of an educational project using modern technologies in the practice of institutions of higher education. The paper discusses the concept, structure and content of an educational project relying on the experience of higher education in Russia and Germany and aims to work towards an understanding of the social significance of future professional activities, primarily concerning the specific problems as well as of the adequacy of social and professional contacts in intercultural communication. Materials and Methods. Based on the subject, object and objectives of the study, the project's methodological plan was implemented in the following stages: project planning, development of the fundamental features of the concept; determination of the project's content; project modeling; introduction to the training of master's students of various specialties at institutions of higher education. The methodological basis of the project consisted of the analysis of intercultural communication between representatives of the German and the Russian linguocultural community as well as the exchange of experience between them and their comparison. Results. Following the study and the exchange of experience between the institutions of higher education of Russia and Germany, the need for an integrative educational course was revealed, aiming at the improvement and optimization of intercultural communication skills at the level of both professional and personal communication with the goal to prepare master's students for their future as researchers and practitioners. The educational project presented in the paper drawing on an eponymous integrative course will increase the efficiency of the training of master's students from various specialized fields and prepare them for successful communication processes with representatives of other linguocultural communities. Discussion and Conclusion. The contents of this paper will be useful for researchers interested in optimizing the preparation of master's students with knowledge in foreign languages by applying international experience.